Firenze in guerra 1940-1944 Catalogo della mostra storico-documentaria (Palazzo Medici Riccardi, ottobre 2014-gennaio 2015) - CAVAROCCHI, Francesca; Galimi, Valeria (Cataloghi e collezioni, 2014)
The volume reproduces the documentary path of the exhibition Florence in the war 1940-1944 promoted by the Historical Institute of the Resistance in Tuscany on the occasion of the 70th anniversary of the Resistance and Liberation. Introductory contributions illustrate the work in progress who accompanied the exhibition project and intend to guide the reader through a series of historiographical questions at the center of the exhibition: the centrality of the 1940-1943 phase, which has hitherto remained in the background, the economic transformations, the knots of consent and social control, the characters of the German occupation, the role of the Church and the complex plot of the Florentine Resistance. The aim of the research was to closely investigate the impact of the war on the population of a large urban area, trying to highlight its specificity and connections with the national framework.